PEMANTAUAN BERBASIS ELEKTRONIK (MEDICATION EVENT MONITORING SYSTEM (MEMS)) UNTUK MENINGKATKAN KEPATUHAN TERHADAP TERAPI ANTIRETROVIRAL PADA ANAK DENGAN INFEKSI HIV/AIDS: TINJAUAN SISTEMATIS - Amelia Hartika Rani; Dwi Budiyati; Rinezia Rinza Farizal; Nyimas Heny Purwati; Irna Nursanti (An Idea Health Journal, 2025)
Tuberculosis is still the main cause of death due to infectious diseases throughout the world. Adherence to antiretroviral (ARV) treatment for HIV infection is a major challenge because it involves many factors. This systematic review follows the PRISMA guidelines checklist and includes articles from various databases, such as Pubmed, Cochrane and Proquest. Quality assessment of each article is carried out using the Critical Appraisal Skills Program (CASP). The search was carried out using the keywords "ARV Therapy, HIV/AIDS Children, Monitoring System, ARV Compliance". Following the inclusion and exclusion criteria 10 relevant articles were identified, excluding duplicates, limited to full papers, open access, and written in English. These findings indicate that electronic-based monitoring shows an increase in medication adherence. Other studies also note that electronic monitoring devices can create a temporary increase in compliance but then decline after some time. These results indicate that electronic-based monitoring can have a significant clinical impact in improving medication compliance. Electronic monitoring is important, especially in children and adolescents who face unique challenges regarding compliance.